An Easy Way To Determine The Flexural Quality Of Asphalt Is Using ASTM D113 – 07 and SNI 2432:2011 - Surya Pratama; Andri Dwi Cahyono; Candra Dwi Saputra; Lina Budi Lestari; Puput Buqin Laso; Febynia Ananda Putri; Puji Rahayu Febyningtyas (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
Asphalt is a material that has non-volatile properties and softens gradually when heated and functions as a binder for aggregates and as a surface covering material to make it impermeable to water. However, asphalt also has a weakness. Namely, it is easy to crack and be damaged when vehicles pass through the main road. To overcome cracked and worn roads, it is necessary to test the ductility of asphalt so that the road becomes flexible/plastic. This ductility test is very important because it greatly affects the pavement layer; Therefore, a ductility test is needed to determine the level of plasticity of an asphalt. The asphalt ductility test method refers to the specifications of ASTM D113 – 07 and SNI 2432:2011 with 3 samples of test objects and a test instrument called a ductilometer of type TAS – 250. Based on the ductility test, the asphalt ductility reaches an average elongation of 117.33 cm; This value indicates that the plasticity level of the asphalt has met the specifications and can be used in sustainable pavement construction layers because it has good plasticity.